2003
DOI: 10.1038/sj.bjc.6600799
|View full text |Cite
|
Sign up to set email alerts
|

Lack of communication between healthcare professionals and women with ovarian cancer about sexual issues

Abstract: Gynaecological cancer has been shown to affect women's sexual functioning, yet evidence suggests that healthcare professionals rarely discuss sexual issues with women diagnosed with a gynaecological cancer. Few studies have investigated why there is a lack of communication between healthcare professionals and women about sexual issues. Our study investigated the attitudes and behaviours of the 27 doctors and 16 nurses treating women with ovarian cancer in our centre towards the discussion of sexual issues, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
286
3
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(313 citation statements)
references
References 19 publications
11
286
3
13
Order By: Relevance
“…Lack of time, lack of privacy and lack of resources have been cited as reasons for not discussing sexual issues with patients (Stead et al 2003). The results of this study highlight that sexual intimacy is an important concern for women with ovarian cancer, regardless of their age.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Lack of time, lack of privacy and lack of resources have been cited as reasons for not discussing sexual issues with patients (Stead et al 2003). The results of this study highlight that sexual intimacy is an important concern for women with ovarian cancer, regardless of their age.…”
Section: Discussionmentioning
confidence: 77%
“…Concerns regarding sexual issues are frequently cited by women with ovarian cancer (Wenzel et al 2002;Carmack Taylor et al 2004) but sexual well being is a neglected area of discussion between health care professionals and women with gynaecological cancers (Corney et al 1992;Corney et al 1993;Cull et al 1993;Stead et al 2001;Stead et al 2003). Lack of time, lack of privacy and lack of resources have been cited as reasons for not discussing sexual issues with patients (Stead et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Stead, Brown, Fallowfield, and Selby (2003) interviewed 43 physicians and nurses regularly treating women with ovarian cancer. Ninety-eight percent reported that they felt sexual issues should be discussed with patients, but only twenty-one percent reported doing so.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Patients can be reluctant to initiate discussions with their providers about sexual function, preferring that providers broach the topic. 7,9 Providers can also be reluctant to raise the subject, 10 especially if they feel they lack the knowledge or skills needed to address this issue, 11 yet there is some evidence that a pre-visit questionnaire can promote patient-provider discussions of sexual dysfunction. 12 Given the availability of treatments and options for referrals for sexual problems, the routine assessment of sexual concerns might reduce barriers to discussing this issue while also providing a means to assess longitudinal changes in an important area of health.…”
Section: Introductionmentioning
confidence: 99%